2006
DOI: 10.1364/josab.23.000461
|View full text |Cite
|
Sign up to set email alerts
|

Experimental comparison of resolution and pattern fidelity in single- and double-layer planar lens lithography

Abstract: An experimental comparison of the performance of single-and double-layer planar lens lithography (PLL) has been carried out. A direct comparison is made with a single 50nm silver lens and a double silver lens with two 30nm layers. Sub-diffraction-limited features have been imaged in both cases, with dense grating periods down to 145nm and 170nm for the single-and doublelayered stacks, respectively. For the same total thickness of silver the resolution limit is qualitatively better for a double layer stack. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 11 publications
0
29
0
1
Order By: Relevance
“…We have explored the imaging properties of both singlelayer [1,4,5] and double-layer silver planar lenses [6]; it has been predicted that for a given mask-resist separation the resolution can be improved by using a multilayer silver lens instead of a single layer [7], but our initial studies are inconclusive in this matter. In addition, we have compared broadband and narrowband exposures through singlelayer silver lenses [8]; broadband exposures offer the advantage of shorter exposure times (and therefore higher throughput for photolithography), however the resolution is compromised due to the dispersive nature of the planar lensing phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…We have explored the imaging properties of both singlelayer [1,4,5] and double-layer silver planar lenses [6]; it has been predicted that for a given mask-resist separation the resolution can be improved by using a multilayer silver lens instead of a single layer [7], but our initial studies are inconclusive in this matter. In addition, we have compared broadband and narrowband exposures through singlelayer silver lenses [8]; broadband exposures offer the advantage of shorter exposure times (and therefore higher throughput for photolithography), however the resolution is compromised due to the dispersive nature of the planar lensing phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Previous analysis [13] performed using the T-matrix technique showed that multi-layer superlenses [4] had better transmission at higher wave numbers (k x / 2S) than equivalent single-layer superlenses (Fig. 1).…”
Section: Resultsmentioning
confidence: 88%
“…These remarkable achievements resulted in further research on possible superlens designs and geometries, with papers published that detailed multi-layer [4], patterned [5] and perforated [6] multipole programming [8] and finite element modelling (FEM) [9,10,11] were used successfully in the past; however, they were all relatively computationally intense and could be slow to produce solutions. Hence, a computationally efficient transfer matrix (T-matrix) method was developed [12] to give an estimate of lens performance using only a few, relatively simple calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The epsilon negative lenses are thin because the surface plasmon modes on the rear surface of the lens can only be excited by an input wave if the front and rear surfaces are strongly coupled [9]. However, it was found experimentally that for thin metallic films the surface roughness increases, which causes the reduction of the image quality and may lead to hotspots in the image plane [21]. The hotspots are caused by the surface roughness of the outermost metallic layer, which builds the lens.…”
Section: Introductionmentioning
confidence: 99%